PEDOT:PSS/PVA/Te ternary composite fibers toward flexible thermoelectric generator. (October 2021) - Yang, Jiaji; Jia, Yanhua; Liu, Youfa; Liu, Peipei; Wang, Yeye; Li, Meng; Jiang, Fengxing; Lan, Xiaoqi; Xu, Jingkun
Abstract: Fiber-based thermoelectric (TE) materials as energy suppliers for mobile or wearable electronic systems have received widespread attention in wearable electronic devices owing to their three-dimensional deformation, lightweight, and excellent electron transfer properties. Herein, ternary thermoelectric fibers are fabricated based on poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), tellurium nanowires (Te-NWs), and polyvinyl alcohol (PVA). The introduction of PVA enhanced the mechanical performance of PEDOT:PSS, and PVA less than 10 wt% has a positive impact on the electrical conductivity ( σ ) of the as-prepared ternary fibers (PEDOT:PSS/PVA/Te-NWs). With the increase in the Te NWs content, the Seebeck coefficient of composite fibers shows the slight increase from 11 to 18 μV K − 1 . By the ethylene glycol (EG) post-process, PEDOT:PSS/PVA/Te NWs composite fibers exhibit further enhanced electrical conductivity of 382.4 S cm −1 and power factor ( σS 2 ) of 8.5 μW m −1  K −2 . Additionally, the as-prepared composite fibers exhibit good mechanical flexibility, which can meet the requirements of textile manufacturing. Furthermore, a fiber-based thermoelectric generator (FTEG) was assembled and gained a maximum output voltage of 5.03 mV by connecting composite fibers and copper wire in series. This work puts eyes on the preparation of advanced FTEG and provides a reference for the energy supply of next-generation electronic products. Graphical abstract: Image 1 Highlights: PEDOT:PSS/PVA/Te-NWs composite fiber has good flexibility. Thermoelectric performance of composite fibers was greatly enhanced by post-treatment. A flexible thermoelectric generator was fabricated based on composite fibers.